EFL TEACHERS’ REASONS, PROBLEMS AND SOLUTIONS OF USING GOOGLE CLASSROOM IN TEACHING AND LEARNING ENGLISH DURING COVID-19 PANDEMIC IN BENGKULU - Desi Suryani; Wisma Yunita; Alamsyah Harahap (Edu-Ling: Journal of English Education and Linguistics, 2021)
Google Classroom is an essential online platform promoting teaching and learning process during Covid-19 pandemic. The research aims to investigate the English as Foreign Language (EFL) teachers’ reasons, problems and analyse their solutions to overcome the problems of using Google Classroom in English teaching and learning process. This research employed a qualitative method. Five EFL teachers were selected as the participant of study. They were selected based on the purposive sampling technique and taken from Senior High Schools in Bengkulu Province. The findings demonstrate that the problems of using Google Classroom are the teachers should prepare the material lesson well and they were expected to be more creative and innovative in making learning media. However, the lack of internet quota and connection made the students got difficulty to receive the learning material or submit assignments. They were also got difficulty to ask directly to the teacher if they did not understand the lesson. In turn, to overcome the problems in teaching and learning English process by using Google Classroom, the teachers participated in training related to the use of Google Classroom for teaching and learning English. In preparing learning media, the teachers provided the material in many forms such as video, voice notes, PDF, or text reading. Furthermore, the teachers invited the students to ask directly by chatting personally or calling by video conference. They also made a lesson video or gave a link of an explanational material video and invited the students to give them feedback on the lesson.